CyberbulIying pada Kolom Komentar Penyandang Disabilitas di Media Sosial TikTok - Sri Maulidiya Ardiyanti; Subyantoro Subyantoro (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This study examines the phenomenon of cyberbullying against people with disabilities in the comment column of the TikTok platform through a forensic linguistic perspective. The focus of the research is directed at the form of speech used by the perpetrator in carrying out verbal attacks. The research method uses a qualitative descriptive approach based on John Searle's speech action theory. Data was collected from comments that contained indications of cyberbullying and analyzed based on speech categories. The results showed that cyberbullying was dominated by assertive (22 findings) and expressive (14 data) speech, with the category of insults as the main instrument of verbal attack. The dominance of assertive speech and expressive insults proves that the perpetrator consciously uses statements to demean people with disabilities, either through derogatory jokes or with explicit intent to insult. These findings confirm that language in the digital space not only serves as a means of communication, but can also be an instrument of symbolic violence that impacts the dignity of the individual. This research is expected to contribute to the development of forensic linguistic studies and become the basis for efforts to prevent and handle cyberbullying against vulnerable groups on social media.